Effectiveness of a comprehensive ambulatory monitoring system for patients with atrial fibrillation after cardioembolic stroke - O. I. Efimova; T. V. Pavlova; L. V. Pyscheva; S. M. Khokhlunov (Российский кардиологический журнал)
Aim. To improve the long-term outcomes of patients with atrial fibrillation (AF) after cardioembolic stroke by creating and testing a comprehensive ambulatory monitoring system.Material and methods. The present study included 139 AF patients after cardioembolic stroke for the period 2016-2019, of which 80 (57,55%) were women and 59 (42,45%) were men. The mean age of the patients was 72,25±6,33years. Before the hospital discharge, all patients signed an informed consent and were randomized into two groups. Patients of the group I (n=72) were followed up during the year in accordance with a specially developed comprehensive ambulatory monitoring system. This system included a rehabilitation program created individually for each patient, monthly visits to a physician-researcher, during which a complex of diagnostic tests was carried out. Also, the changes of complaints, symptoms, and medical adherence were assessed. The latter was corrected. A physician talked with the patient's relatives about the need to comply with the recommended medication regimen, supporting the motivation for treatment. Patients of group II (n=67) were followed up at the primary care level in accordance with the current program, and a control visit to was performed for them once — after 12 months.Results. After one-year follow-up, a significant decrease in all-cause mortality was obtained in the first group in comparison with the second one: 3 (4,17%) and 18 (26,87%) deaths, respectively (p=0,021).In addition, in group II, a relationship was found between the death and absence of anticoagulant therapy (odds ratio, 7,68; 95% confidence interval, 1,59-37,03; p=0,01). The ROC analysis confirmed the relationship between the absence of anticoagulant therapy and death, while the regression quality was good (area under the curve, 0,77, sensitivity — 94,74%, specificity — 59,17%).Conclusion. Comprehensive ambulatory monitoring program for AF patients after cardioembolic stroke has proven high effectiveness, and its widespread practice is an urgent task of modern healthcare.